Alterations in the memory of rat offspring exposed to low levels of fluoride during gestation and lactation: Involvement of the α7 nicotinic receptor and oxidative stress - Bartos, Mariana (2018)
Daily exposure to fluoride (F) depends mainly on the intake of this element with drinking water. When administered during gestation and lactation, F has been associated with cognitive deficits in the offspring. However, the mechanisms underlying the neurotoxicity of F remain obscure. In the current study, we investigated the effects of oral exposure to low levels of F during the gestational and lactation periods, on the memory of adult female rat offspring. We also considered a possible underlying neurotoxic mechanism. Our results showed that this exposure reduced step-down latency in the inhibitory avoidance task, and decreased both mRNA expression of the α7 nicotinic receptor (nAChR) and catalase activity in hippocampus. Our data indicates that low F concentrations administrated during gestation and lactation decrease the memory of 90-day-old female offspring. This suggests that the mechanism might be connected with an α7 nAChR deficit in the hippocampus, induced by oxidative stress.